Aspiration pneumonia in the setting of diffuse esophageal retention cysts: An autopsy case report - Daffolyn Rachael Fels Elliott; Walter E. Finkbeiner; Gabrielle Rizzuto (Elsevier, 2018)
Esophageal retention cysts are rare findings at autopsy and an unusual cause of dysphagia. In the diffuse form they have been termed esophagitis cystica. We present an autopsy case of aspiration pneumonia associated with both oropharyngeal dysphagia due to prior stroke and obstructive esophageal dysphagia due to florid esophagitis cystica. We describe the immunohistochemical profile of secreted and membrane-associated mucins to confirm the origin of the retention cysts from dilated excretory ducts of submucosal glands. To our knowledge, this is the first report to describe esophagitis cystica contributing to cause of death at autopsy. Keywords: Esophageal retention cyst, Esophagitis cystica, Mucocele